Analisis Faktor-faktor yang Mempengaruhi Tindakan Kecurangan Pengelolaan Anggaran Badan Usaha Milik Desa (BUMDes) - Ni Luh Candra Dewi; I Nyoman Sujana (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
The purpose of this research is (1) to find out what factors influence the fraudulent act of budget management and (2) which factors are the most dominant in influencing the fraudulent act of budget management in Village-Owned Enterprises (BUMDes) in Gerokgak District. This type of research is a quantitative study using a factorial research design. The population of this study were all BUMDes administrators in Gerokgak District. Data collection using a questionnaire was analyzed using factor analysis assisted by the SPSS 24.0 for Windows program. The results showed that the factors that influence the fraudulent actions of BUMDes budget management in Gerokgak District consist of 2 factor components, namely: factor 1 (pressure) consists of pressure, arrogance, competence and factor 2 (opportunity) consists of opportunity and razionalization factors. The most dominant factors affecting the fraudulent act of BUMDes budget management in Gerokgak District are as follows. (1) Component factor 1 (pressure) with a varimax rotation of 52.170% with the dominating factor, namely pressure which has the highest loading factor of 0.898; and (2) component factor 2 (opportunity) with a varimax rotation of 21.237% with the dominant factor, namely the opportunity which has the highest loading factor of 0.864.